Short- and Medium-Term Effects of Informal Eldercare on Labor Market Outcomes - Dörte Heger; Thorben Korfhage (Feminist Economics, 2020)
Informal caregivers, often family members, provide valuable services to elderly persons with long-term care needs. However, the time commitment of caregiving often competes against time spent in the labor force. In addition to the momentary trade-off, long-term consequences are possible since older workers in particular might find it difficult to reenter the labor market after a period of caregiving. While several studies document a negative relationship between caregiving and paid work, little is known about whether this effect persists over time. Analyzing a large panel data set of fifteen European countries and Israel, this study shows that care provision for an elderly parent has negative effects on employment rates and paid working hours for both men and women. While men are more likely to drop out of the labor force, especially in response to continuous caregiving, women, on average, also reduce their paid working hours.
Keywords: J14; J22; 330; Long-term care; informal care; labor market outcomes; short- and medium-term effects